COMMUNITY STRUCTURE OF GASTROPOD (MOLLUSCA) IN THE MANGROVE ECOSYSTEM OF PURNAMA, DUMAI CITY RIAU PROVINCE - Bahari, Sandy; Nasution, Syafruddin; Efriyeldi, Efriyeldi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2020)
This research was conducted in January 2019 on the mangrove ecosystem of Purnama Dumai City, Riau Province with the aim to determine the structure of the gastropod community which includes the type, density, diversity, distribution patterns and similarity of the community. The method used is a survey method, where the sampling location consists of 5 research stations. The type and density of gatropods are determined by drawing a transect line from the mangrove forest towards the highest tide line. The transect was placed in 3 1x1 m2 maps with a distance of 10 m. The results showed that the Gastropod species found consisted of 6 species, namely Nerita costata, Telebrelia sulcata, Cicopreus capucinus, Telescopium telelescopium, Littorina sp, Volema myristican. Based on ANOVA analysis, gastropod density between stations was not significantly different in the waters of Purnama Village, Dumai City. Diversity is categorized as medium, Uniformity is categorized as balanced and the dominance of certain types. While the overall distribution pattern of Gastropods tends to be clustered.